Characterization of conformational transition of polymers with low molecular weights in solutions by fluorescence resonance energy transfer. (2nd March 2020) - Qin, Linlin; Zhao, Ning; Sha, Ye; Chen, Hu; Li, Linling; Zhou, Dongshan; Chen, Wei; Xue, Gi; Jia, Xudong
Abstract: The conformations of polymers in solutions are of great importance, and scattering techniques prevail in detecting these conformations. However, most studies only focus on polymer species with high molecular weights or those well above their entanglement molecular weights, and studies on polymer solutions with low molecular weights, e.g., lower than 10, 000 Da, are lacking. Here, the conformation of low molecular weight polymers in solutions with different concentrations was investigated via fluorescence resonance energy transfer (FRET). Based on a site-specific chromophore-labeling protocol, the conformational information of the polymer was inferred from the end-to-end FRET response. In principle, the FRET efficiency increases with increasing polymer concentration since the size of the polymer coil decreases. For low molecular weight polymers, the trend of the FRET efficiency shows the opposite effect as the polymer concentration increases, which is rationalized by the counterbalance of the intrinsic size contraction (static item) of and terminal diffusion (dynamic item) from the polymer coil. The universality of this law is verified by similar results from the polymethyl methacrylate (PMMA) system. This work provides new efforts for the conformational study of polymer solutions and demonstrates that the diffusion effect should be taken into account for low molecular weight polymers but is negligible for polymers with high molecular weights. Graphical abstract: Image 1